How do you use the quadratic formula to solve $4{x^2} + 16x + 15 = 0$ ?
Answer
Verified
440.4k+ views
Hint:First we will reduce the equation further if possible. Then we will try to factorise the terms in the equation. Then solve the equation by using the quadratic formula and finally evaluate the value of the variable accordingly.
Complete step by step answer:
We will start off by reducing any reducible terms in the equation.
$4{x^2} + 16x + 15 = 0$
Now we will factorise the terms in the equation.
$4{x^2} + 16x + 15 = 0$
Now we will try to factorise by using the quadratic formula which is given by $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$
To substitute the values, we first compare and evaluate the values from the general form of the quadratic equation. The general form of the quadratic equation is given by $a{x^2} + bx + c = 0$. When we compare the terms, we get the values as,
$a = 4 \\
\Rightarrow b = 16 \\
\Rightarrow c = 15 \\ $
Now substitute all these values in the quadratic formula, to evaluate the value of the variable.
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {{{(16)}^2} - 4(4)(15)} }}{{2(4)}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {(256) + 4(4)(15)} }}{{2(4)}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {(256) + 240} }}{8} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {496} }}{8} \\
\Rightarrow x = \dfrac{{ - 16 \pm 4\sqrt {31} }}{8} \\
\Rightarrow x = \dfrac{{ - 4 \pm \sqrt {31} }}{2} \\ \]
Now we solve for the value $x$ separately.
So, we get the values as,
\[x = \dfrac{{ - 4 - \sqrt {31} }}{2} \\
\therefore x = \dfrac{{ - 4 + \sqrt {31} }}{2} \\ \]
Hence, the total valid solutions of the quadratic equation $4{x^2} + 16x + 15 = 0$ are $\dfrac{{ - 4 - \sqrt {31} }}{2},\dfrac{{ - 4 + \sqrt {31} }}{2}$.
Additional information:
The quadratic formula is the formula that provides the solution to a quadratic equation. there are two ways of solving a quadratic equation instead of using the quadratic formula, such as factoring, completing the square, graphing and others.
Note:While splitting the middle term be careful. After splitting the middle term Do not solve all the equations simultaneously. Solve all the equations separately, so that you don’t miss any term of the solution. Check if the solution satisfies the original equation completely. If any term of the solution doesn’t satisfy the equation, then that term will not be considered as a part of the solution.
Complete step by step answer:
We will start off by reducing any reducible terms in the equation.
$4{x^2} + 16x + 15 = 0$
Now we will factorise the terms in the equation.
$4{x^2} + 16x + 15 = 0$
Now we will try to factorise by using the quadratic formula which is given by $x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$
To substitute the values, we first compare and evaluate the values from the general form of the quadratic equation. The general form of the quadratic equation is given by $a{x^2} + bx + c = 0$. When we compare the terms, we get the values as,
$a = 4 \\
\Rightarrow b = 16 \\
\Rightarrow c = 15 \\ $
Now substitute all these values in the quadratic formula, to evaluate the value of the variable.
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {{{(16)}^2} - 4(4)(15)} }}{{2(4)}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {(256) + 4(4)(15)} }}{{2(4)}} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {(256) + 240} }}{8} \\
\Rightarrow x = \dfrac{{ - 16 \pm \sqrt {496} }}{8} \\
\Rightarrow x = \dfrac{{ - 16 \pm 4\sqrt {31} }}{8} \\
\Rightarrow x = \dfrac{{ - 4 \pm \sqrt {31} }}{2} \\ \]
Now we solve for the value $x$ separately.
So, we get the values as,
\[x = \dfrac{{ - 4 - \sqrt {31} }}{2} \\
\therefore x = \dfrac{{ - 4 + \sqrt {31} }}{2} \\ \]
Hence, the total valid solutions of the quadratic equation $4{x^2} + 16x + 15 = 0$ are $\dfrac{{ - 4 - \sqrt {31} }}{2},\dfrac{{ - 4 + \sqrt {31} }}{2}$.
Additional information:
The quadratic formula is the formula that provides the solution to a quadratic equation. there are two ways of solving a quadratic equation instead of using the quadratic formula, such as factoring, completing the square, graphing and others.
Note:While splitting the middle term be careful. After splitting the middle term Do not solve all the equations simultaneously. Solve all the equations separately, so that you don’t miss any term of the solution. Check if the solution satisfies the original equation completely. If any term of the solution doesn’t satisfy the equation, then that term will not be considered as a part of the solution.
Recently Updated Pages
A uniform rod of length l and mass m is free to rotate class 10 physics CBSE
Solve the following pairs of linear equations by elimination class 10 maths CBSE
What could be the possible ones digits of the square class 10 maths CBSE
Where was the Great Bath found A Harappa B Mohenjodaro class 10 social science CBSE
PQ is a tangent to a circle with centre O at the point class 10 maths CBSE
The measures of two adjacent sides of a parallelogram class 10 maths CBSE
Trending doubts
Imagine that you have the opportunity to interview class 10 english CBSE
Find the area of the minor segment of a circle of radius class 10 maths CBSE
Fill the blanks with proper collective nouns 1 A of class 10 english CBSE
Frogs can live both on land and in water name the adaptations class 10 biology CBSE
Fill in the blank One of the students absent yesterday class 10 english CBSE
Write a letter to the Principal of your school requesting class 10 english CBSE